Implementasi Kebijakan Peraturan Daerah Nomor 2 Tahun 2014 tentang Lahan Pertanian Pangan Berkelanjutan dan Lahan Cadangan Pertanian Pangan Berkelanjutan di Kabupaten Temanggung - Sapto Purnomo Wibowo; Wiwik Widayati; Lusia Astrika (Journal of Politic and Government Studies, 2015)
ABSTRACTPolicy Implementation Regional Regulation No. 2 of 2014 on Agricultural Land and Land Reserves Sustainable Agriculture Sustainable Food in Temanggung RegencyPolicy Implementation Regional Regulation No. 2 of 2014 on Agricultural Land and Land Reserves Sustainable Agriculture Sustainable Food at Temanggung Regency is a policy made by the Government, namely the Regional Regulation No. 2 of 2014 on the Protection of Agricultural Land and Land Reserves Sustainable Agriculture Sustainable Food. This policy is a policy that has the objective to control and protect LP2B.menjamin LP2B availability, and achieve independence, resilience, and food sovereignty at Temanggung Regency.This study is a qualitative study with the primary objective to describe in depth the Policy Implementation Regional Regulation No. 2 of 2014 on Agricultural Land and Land Reserves Sustainable Agriculture Sustainable Food Temanggung Regency. Data collection techniques in this study using in-depth interviews and documentation and document analysis. Analysis of the data in this study include stage data reduction, data presentation, and data verification or conclusion.From the results of this study concluded that the policy Regional Regulation No. 2 of 2014 on Agricultural Land and Land Reserves Sustainable Agriculture Sustainable Food in Temanggung Regency has been running optimally implementation, the socialization process is carried out in stages, beginning after the passing of Governor Regulation No. 2 of the Regional Regulation 2014 governing the Protection of Agricultural Land Sustainable Temanggung Regency of Agricultural Land and Land Reserves Sustainable Agriculture Sustainable Food at Temanggung Regency. Socialization starts from dissemination to government officials in Waterford District, then dissemination to the public.For that in the aspect of law enforcement in order to be confirmed by follow-up acts irregularities, misuse of land that is not as it should be appropriate sanctions violations that have been set up and published in Regional Regulation No. 2 of 2014 on the Protection of Agricultural Land Husbandry and Food Agricultural Land Reserves Sustainable.Keywords: Implementation; Sustainable Agricultural Land; Sustainable Food Agriculture Land Reserve; Temanggung Regency